Impact of interferon-induced transmembrane protein 3 gene rs12252 polymorphism on COVID-19 mortality. (September 2022) - Ahmadi, Iraj; Afifipour, Alireza; Sakhaee, Fatemeh; Zamani, Mohammad Saber; Mirzaei Gheinari, Fahimeh; Anvari, Enayat; Fateh, Abolfazl
Highlights: MAF of IFITM3 rs12252 (C) was significantly more frequent in dead patients than in improved cases. The COVID-19 mortality rate was related to IFITM3 rs12252 CC genotype. IFITM3 plays an important role in innate and adaptive immune response. Abstract: Background and aims: Interferon-induced transmembrane protein 3 ( IFITM3 ) plays a critical role in the adaptive and innate immune response by preventing membrane hemifusion between the host and viral cell cytoplasm. This study aimed to evaluate whether IFITM3 rs12252 polymorphism is related to an increased mortality rate of coronavirus disease 2019 (COVID-19). Methods: The IFITM3 rs12252 polymorphism was genotyped using the amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) in 548 dead and 630 improved patients positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Results: In the present study, the minor allele frequency of IFITM3 rs12252 (C) was significantly more frequent in dead patients than in improved cases. The results of the multivariate logistic regression analysis indicated that the lower lipid profiles, PCR Ct value, 25-hydroxyvitamin D, and uric acid and higher levels of erythrocyte sedimentation rate (ESR), liver enzymes, and creatinine, and IFITM3 rs12252 CC genotypes were related to the COVID-19 infection mortality. Conclusions: In summary, our findings suggested a possible link between the mortality of COVID-19 infection, the CC genotypes of IFITM3 rs12252, and clinical parameters. Further investigations are required worldwide to prove the link relationship of COVID-19 mortality with host genetic factors.